Dermoid Cyst of the retroauricular region: a rare clinicopathological entity - Alberici, Maria Paola; Franzini, Sebastiano; Tassi, Sauro; Di Lella, Filippo; Negri, Maurizio (Acta Biomedica Atenei Parmensis, 2021)
Dermoid cysts (DC) of the head and neck are rare congenital anomalies derived from entrapment of ectodermal cells at lines of fusion in the embryo into mesoderm. We describe a 22-years-old female with an unusual presentation of DC in the subcutaneous tissue of the retro-auricular region, confirmed by pathological examination of the surgically removed specimen. A DC in this region is rare and may be misdiagnosed as a retroauricular lymph node. Complete excision of the lesion must be achieved with pathology study to confirm diagnosis.